A Successful Treatment Regimen for the Prevention of Sinusitis after Maxillary Sinus Floor Elevation Surgery in a High-Risk Case - Suzuki-Yamazaki, Mikiko; Takahashi, Keiso; Takada, Satoshi; Kato, Yasumasa; Baba, Yuh (Case Reports in Otolaryngology, 2020)
Maxillary sinus floor elevation (sinus lift) is a widely recognized dental-surgical approach for dental implant placement. However, for an otorhinolaryngological high-risk patient with severe anatomic-structural impairments of the maxillary sinus drainage pathway, surgical intervention is recommended before sinus lift to avoid postsinus lift maxillary sinusitis. Here, we show a case that postsinus lift maxillary sinusitis in such a high-risk patient was noninvasively prevented by the collaboration of otorhinolaryngologist and dentist. A 48-year-old Japanese male intended to undergo a sinus lift for dental implant placement by periodontist. Otorhinolaryngologist found septal deviation, concha bullosa, the presence of Haller cell, and nasal mucosal swelling by the nasal allergy, while no sinusitis and diagnosed him as a “high-risk case” for postsinus lift maxillary sinusitis. The patient was administered preoperative topical steroid and leukotriene receptor antagonist in addition to perioperative antibiotic prophylaxis so that his complication was noninvasively prevented. Thus, this case suggested that consultation from dentist to otorhinolaryngologist provides benefit to the patients who have been diagnosed as “high-risk case” for postsinus lift maxillary sinusitis.